Implementing PODS (Patient Oriented Discharge Summary) in an acute medical urban health setting in Vancouver, Canada - Agnes Black; Suzanne Nixon; MacLeod Meghan; Christine Wallsworth; Lena Cuthbertson; Beena Parappilly; Jay MacDonald; Kate McNamee; Cheryl Prinzen (The Beryl Institute, 2021)
The transition from hospital to home or community is a vulnerable time for patients and families, who face risks associated with misunderstanding instructions about medications, self-monitoring and when to seek emergency care. The quality of the discharge process can have a significant impact on patient confidence, overall patient experience, ability to manage health at home, and hospital readmission rates. Patient Oriented Discharge Summary (PODS) is a standardized form and set of process changes, utilized to overcome communication barriers faced at discharge. We implemented PODS in two Acute Medicine units of a tertiary care hospital in western Canada and used a mixed-methods approach to evaluate the four process changes (PODS form, use of teach-back, engagement of caregivers in discharge teaching, follow-up phone calls). Evaluation showed that 60% of patients received PODS and 87% found the form helpful. There was a large increase in the percentage of patients who felt adequately prepared at the time of discharge, and a 10% increase in the number of patients who rated their overall hospital experience positively. Healthcare providers reported that using PODS they were more confident that patients were adequately prepared to return home. The update of PODS on the implementation units has been sustained at 60% for 18 months. Implementation of the PODS form and process can be accomplished with an interdisciplinary team, leadership support and by working closely with Patient Family Partners. PODS can improve the discharge process even in the complex urban acute medical environment in ways that offer wide-reaching benefits. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.